Zeolite, Humus and Biochar Remediation of Heavy Metal Contaminated Soil: A Review - Li, Yan; Lu, Nan; Luo, Yuhu (International Journal of Natural Resources and Environmental Studies, 2024)
With the swift advancement of industrialization and urbanization, soil heavy metal contamination has grown increasingly severe, presenting a grave menace to the environment and human health. As efficacious soil remediation substances, zeolite, humus, and biochar exhibit considerable potential in the treatment of heavy metal pollution. In this article, the research progress of zeolite, humus, and biochar in the remediation of heavy metal pollution in soil was reviewed, the remediation mechanisms, influencing factors, and practical application effects were analyzed, and the future research direction was prospected. Through comprehensive analysis and discussion, the aim is to offer useful references for the control of soil heavy metal pollution.